Introduction to the Social Environment in Early Childhood - Mastini, Luh; Musafir, Musafir; Kariani, Ni Luh; Hasanah, Ihsan; Marni, Marni (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Introduction to the environment and social aspects in early childhood is an essential factor in shaping children's character and social skills. The family, as the first social environment, played a primary role in teaching fundamental values such as togetherness, affection, and responsibility. This study aimed to describe the scope of introducing social sciences to early childhood. The research method used was a literature study, involving the analysis of journals and related literature. The results showed that the family served as a vital foundation in children's social development through the formation of basic values and the teaching of social roles. Children were also introduced to self-identity, emotions, and their responsibilities in daily life. Early Childhood Education (ECE) played a strategic role in integrating this understanding into educational programs, which did not solely focus on academic aspects but also emphasized character building. Through comprehensive and systematic introduction, children could grow into independent, empathetic, and responsible individuals, ready to face a harmonious social life in the future.